CONSTRUCT VALIDITY OF COUNTERPRODUCTIVE WORK BEHAVIOR-ORGANIZATIONAL MEASURING TOOLS - Baquandi Lutvi Yoseanto (Media Inovasi Pendidikan dan Publikasi, 2024)
Counterproductive work behavior-organizational (CWB-O) is a variety of intentional behavior that harms/endangers the organization. Counterproductive organizational work behavior is one of the serious problems faced by companies because it is related to material/financial losses. This research aims to test the construct validity of counterproductive organizational work behavior questionnaire. The approach in this research is quantitative with a sample of 209 participants. Data collection was carried out by simple random sampling using a g-form questionnaires. The measuring tool in this research is the Workplace Deviance Scale by Bennett & Robinson. The analysis method uses the CFA test using structural equation modeling. The results of this study indicate that the CFA model is fit with details: Chi Square=69.193 (p=0.000), RMSEA=0.077, GFI=0.933, CFI=0.954, and TLI=0.933. The model modification was to remove 17 manifest variables and covariate between 4 pairs of error variables. The results of this research can be used by the wider community, especially companies or organizations that want to see the level of counterproductive work behavior of employees in the workplace so that preventive or corrective action can be taken.